2020
DOI: 10.1111/jace.17467
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the sinterability and electrical properties of BaZr0.1Ce0.7Y0.2O3‐δ proton‐conducting ceramic electrolyte

Abstract: A novel strategy was proposed to enhance the sinterability and electrical properties of BaZr 0.1 Ce 0.7 Y 0.2 O 3-δ (BZCY) proton-conducting electrolyte by adding 10 wt.% La 0.9 Sr 0.1 Ga 0.8 Mg 0.2 O 3-δ (LSGM) to form a 90 wt.% BZCY-10 wt.% LSGM (BL91) composite electrolyte. XRD patterns showed that no reaction occurred between How to cite this article: Yu S, Wang Z, Yang L, et al. Enhancing the sinterability and electrical properties of BaZr 0.1 Ce 0.7 Y 0.2 O 3-δ proton-conducting ceramic electrolyte.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 72 publications
(170 reference statements)
0
11
0
Order By: Relevance
“…In order to reduce the effects of undesirable electron transport of PCMs on the output properties of protonic ceramic electrochemical cells, the latter should be operated at low- and intermediate-temperature ranges. This strategy is constantly developing due to the design of new electrolyte materials, 121,138–141 novel thin-film technologies, 32,142,143 and innovative highly active electrode systems. 144–148…”
Section: Electronic Transport Of Individual Proton-conducting Materialsmentioning
confidence: 99%
“…In order to reduce the effects of undesirable electron transport of PCMs on the output properties of protonic ceramic electrochemical cells, the latter should be operated at low- and intermediate-temperature ranges. This strategy is constantly developing due to the design of new electrolyte materials, 121,138–141 novel thin-film technologies, 32,142,143 and innovative highly active electrode systems. 144–148…”
Section: Electronic Transport Of Individual Proton-conducting Materialsmentioning
confidence: 99%
“…To probe the bulk and grain boundary effects, we assembled the fuel cell devices using the BZY pellets with and without sintering as the electrolyte, which was sandwiched between the two NCAL electrodes. The EIS curves obtained on BZY without and with sintering were compared as shown in Figure 2 h, where the results were modeled through an equivalent circuit (inset) mode of L s R b ( R gb CPE gb )( R ct CPE ct ) as reported previously, 27 , 28 where R b , R gb, and R ct stand for resistance of the bulk, the grain boundary, and the overall electrode, respectively. After high-temperature sintering of BZY, the resistance of the grain boundary increased from 0.59 to 2.95 Ω, also listed in Table S1 of the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…The data reported in the literature related to LaSrGaO 4 and LaSrGa 3 O 7 are attributed to high-resistance impurity phases, which are responsible for the degradation of the electrical properties of LSGM. 32,33 The effects of non-stoichiometric changes on phase purity and impurity phase content were determined by performing XRD in the range of 2 θ = 28–35° as shown in Fig. S2†, and with rGO content doped in LSGM, no significant structural changes or phase segregations were detected.…”
Section: Resultsmentioning
confidence: 99%
“…Literature studies also reveal the presence of secondary phases in published data. [32][33][34][35] However, Marrero-López et al 36 reported studies related to the total conductivity of LSGM and claimed that conductivity is not much affected by the presence of LaSrGa 3 O 7 and LaSrGaO 4 , even for samples containing considerable amounts of impurities. In each case, the sintering temperature chosen to synthesize the LSGM electrolyte was found to be 1450 C to get the minimum quantity of LaSrGa 3 O 7 , based on previous studies reported elsewhere.…”
Section: Phase Composition Analysis Of the Ceramic And Compositementioning
confidence: 99%